A review on superstructure optimization approaches in process system engineering - Mencarelli, Luca; Chen, Qi; Pagot, Alexandre; Grossmann, Ignacio E. (Computers & chemical engineering, 2020)
•Critical review of state-of-the-art in superstructure-based process synthesis.•Tools and methods for superstructure generation.•Superstructure representation impacts on algebraic modeling and optimization.•Comparison with superstructure-free (evolutionary) design strategies. In this paper, we survey the main superstructure-based approaches in process system engineering, with a particular emphasis on the existing literature for automated superstructure generation. We examine both classical and more recent representations in terms of generality, ease of use, and tractability. We also discuss the implications that different representations may have on strategies for algebraic modeling and optimization. We then review the state-of-the-art in software implementations to support synthesis. Finally, we examine the use of evolutionary—recently referred to as superstructure-free—approaches, in which algorithmic procedures dynamically generate and evaluate candidate process structures.